INTERLOCKED NAILING OF COMMINUTED FRACTURES SHAFT OF FEMUR SHAHID SULTAN - SULTAN, SHAHID (Journal of Ayub Medical College Abbottabad, 2001)
Background: Comminuted fracture shaft of femur are difficult to treat. Internal fixation with ordinary nail does not hold the fracture fragments while osteosynthesis with plates and screws docs not always produce stable fixation and involves an increased risk of infection. Methods: Thirty-six comminuted fractures shaft of femur were treated with closed interlocked nailing. There were twenty closed and sixteen open fractures. Results: Thirty-six fractures united without additional surgical intervention. Average time to union was 34 weeks (range 26 to 64 weeks). 'In five patients secondary bone grafting was done. Conclusion: Closed Interlocked nailing is the treatment of choice for most comminuted fracture shaft of femur.